2017
DOI: 10.3847/1538-4357/aa7aa0
|View full text |Cite
|
Sign up to set email alerts
|

Herschel and Hubble Study of a Lensed Massive Dusty Starbursting Galaxy at z ∼ 3

Abstract: We present the results of combined deep Keck/NIRC2, HST/WFC3 near-infrared and Herschel far infrared observations of an extremely star forming dusty lensed galaxy identified from the Herschel Astrophysical Terahertz Large Area Survey (H-ATLAS J133542.9+300401). The galaxy is gravitationally lensed by a massive WISE identified galaxy cluster at z ∼ 1. The lensed galaxy is spectroscopically confirmed at z = 2.685 from detection of CO(1 → 0) by GBT and from detection of CO(3 → 2) obtained with CARMA. We use the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 190 publications
1
13
0
Order By: Relevance
“…All samples cover a similar range in t dep , but the average t dep for the (higher M gas ) high-z samples appear lower. Top right: the r 31 brightness temperature ratio of VLASPECS galaxies (green circles) is similar to that of strongly lensed z∼3 Lyman-break galaxies (red triangles; Riechers et al 2010), z>2 main-sequence galaxies from the PHIBSS survey (gray crosses; Bolatto et al 2015), and z>2 dusty star-forming galaxies (DSFGs; blue squares; compilation from Sharon et al 2016; including data from Danielson et al 2011;Ivison et al 2011;Riechers et al 2011aRiechers et al , 2011bRiechers et al , 2013Thomson et al 2012;Fu et al 2013;Sharon et al 2013Sharon et al , 2015 other DSFGs shown as light gray squares are from Nayyeri et al 2017;Dannerbauer et al 2019;Harrington et al 2019;Leung et al 2019;Sharon et al 2019) and clustered DSFGs (dark gray squares; Bussmann et al 2015;Gómez-Guijarro et al 2019), but ∼2 times higher on average than BzK-selected main-sequence galaxies at z∼1.5 (magenta crosses; Daddi et al 2015). Nearby galaxy samples from the xCOLD GASS survey (Lamperti et al 2020) and two studies of infrared-luminous galaxies (Yao et al 2003;Papadopoulos et al 2012) are shown for comparison.…”
Section: Gas Masses Depletion Times and Line Ratiosmentioning
confidence: 89%
“…All samples cover a similar range in t dep , but the average t dep for the (higher M gas ) high-z samples appear lower. Top right: the r 31 brightness temperature ratio of VLASPECS galaxies (green circles) is similar to that of strongly lensed z∼3 Lyman-break galaxies (red triangles; Riechers et al 2010), z>2 main-sequence galaxies from the PHIBSS survey (gray crosses; Bolatto et al 2015), and z>2 dusty star-forming galaxies (DSFGs; blue squares; compilation from Sharon et al 2016; including data from Danielson et al 2011;Ivison et al 2011;Riechers et al 2011aRiechers et al , 2011bRiechers et al , 2013Thomson et al 2012;Fu et al 2013;Sharon et al 2013Sharon et al , 2015 other DSFGs shown as light gray squares are from Nayyeri et al 2017;Dannerbauer et al 2019;Harrington et al 2019;Leung et al 2019;Sharon et al 2019) and clustered DSFGs (dark gray squares; Bussmann et al 2015;Gómez-Guijarro et al 2019), but ∼2 times higher on average than BzK-selected main-sequence galaxies at z∼1.5 (magenta crosses; Daddi et al 2015). Nearby galaxy samples from the xCOLD GASS survey (Lamperti et al 2020) and two studies of infrared-luminous galaxies (Yao et al 2003;Papadopoulos et al 2012) are shown for comparison.…”
Section: Gas Masses Depletion Times and Line Ratiosmentioning
confidence: 89%
“…of SMGs match these criteria (Bothwell et al 2013b; see also Ivison et al 2011). including the lensed dusty star-forming galaxy, NA.v1.489, which is also a SMG (Nayyeri et al 2017), as well as most compact star-forming galaxies. While it can be argued that their higher SFE and lower f gas might be attributed to the choice of CO-to-H 2 conversion factor that could vary by a factor of ∼4, we highlight that the discrepancy still stands if we only consider the galaxies with [C i] measurements and thus unaffected by this systematic uncertainty.…”
Section: A Synthetic Picture: Quenching Via Gas Depletionmentioning
confidence: 99%
“…We also overplot a compilation of star-forming galaxies at z = 1.3−4 with M H 2 measurements. These include the colour-selected sample 8 of Daddi et al (2010) and the PHIBBS sample (Tacconi et al 2013) which are both CO surveys, the ALMA dust continuum samples of SFGs at z = 1.3−3.2 (Elbaz et al 2018) and at z = 2.53 (Tadaki et al 2015), as well as several lensed SFGs with dust continuum and CO detections (Bothwell et al 2013a;Sharon 2013;Dessauges-Zavadsky et al 2015;Nayyeri et al 2017). Compact SFGs (Tadaki et al 2015(Tadaki et al , 2017Spilker et al 2016;Barro et al 2017;Popping et al 2017a) and luminous submillimeter galaxies (SMGs) from the sample of Bothwell et al (2013a) are also plotted.…”
Section: A Synthetic Picture: Quenching Via Gas Depletionmentioning
confidence: 99%
“…Our new analysis reveals a large, highly obscured stellar mass, similar to the most massive and extreme SMGs during the peak of star formation (e.g., Hainline et al 2011;Ma et al 2015;Schinnerer et al 2016;Miettinen et al 2017;Nayyeri et al 2017). However, as already discussed in Conley et al (2011) andWardlow et al (2013), HLock01-R has a moderately low q IR =1.8±0.4 (which is the logarithmic ratio of L IR and the rest-frame 1.4 GHz flux density), compared with the mean value for HerMES sources (q IR =2.40±0.12; Ivison et al 2010a).…”
Section: Physical Propertiesmentioning
confidence: 99%